Health and a healthy lifestyle - Abdullayeva, Mekhriban Rayimberganovna; Ismailova, Aziza (Science and Education, 2023)
This article provides information on health and a healthy lifestyle, which is one of the most topical issues, and partially solves the existing problems. According to the Charter of theWorld Health Organization, health is a state of physical,mental and social well-being. Therefore, health is a blessing for everyone, happiness isa necessary condition for increasing labor productivity, the economic power of the country and the well-being of the people. Sanology is the study of health and teachesabout public health, health responsibilities, and how to accomplish them. The diversityof factors that affect or pose a threat to public health is determined by theirsimultaneous impact.